1991
DOI: 10.1093/infdis/163.3.454
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Hepatitis B Virus Infection in Homosexual Men and Its Relation to Prior Human Immunodeficiency Virus Infection

Abstract: To investigate the effect of human immunodeficiency virus type 1 (HIV-1) infection on subsequent hepatitis B virus (HBV) infection, HIV antibody was sought in homosexual men who developed HBV infection during a hepatitis B vaccine trial. Among 134 unvaccinated HIV-1-negative men, 7% became HBV carriers, 64% had viremia, and 42% had clinical illness. Among vaccinated HIV-1-negative men, HBV infection severity decreased with number of vaccine doses administered. When adjusted for prior hepatitis B vaccination st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(123 citation statements)
references
References 20 publications
6
114
0
3
Order By: Relevance
“…An estimated 240 million people are chronically infected with hepatitis B (HBsAg positive > 6 months), and more than 686 000 people die annually due to its complications [38].Perinatal transmission, infants, and children under 5 infections with immature immune systems account for 90% of chronic HBV infections while 95% of adult infections recover fully [39][40][41]. Chronic hepatits B also occur also in immunosuppressed persons [42]. Horizontal transmission occurs when susceptible individuals and households come in contact to infected blood, and body fluids.…”
Section: Hepatitis B Surface Antigen (Hbsag)mentioning
confidence: 99%
“…An estimated 240 million people are chronically infected with hepatitis B (HBsAg positive > 6 months), and more than 686 000 people die annually due to its complications [38].Perinatal transmission, infants, and children under 5 infections with immature immune systems account for 90% of chronic HBV infections while 95% of adult infections recover fully [39][40][41]. Chronic hepatits B also occur also in immunosuppressed persons [42]. Horizontal transmission occurs when susceptible individuals and households come in contact to infected blood, and body fluids.…”
Section: Hepatitis B Surface Antigen (Hbsag)mentioning
confidence: 99%
“…Additionally, HIV patients have a higher risk of chronic infection after exposure, and experience faster progression to cirrhosis and HBV-related complications. 2,45 Further, chronic HBV is associated with poorer HIV outcomes, with a nearly twofold higher risk of AIDS/death. 46 Hence, all HIV-infected persons without evidence of HBV immunity should be vaccinated.…”
Section: Pneumococcalmentioning
confidence: 99%
“…This is comparable to that observed in other HIV cohorts. 15,16 It has been shown that the incidence of chronic HBV infection has decreased since the HAART era. 9 Although we were unable to subdivide our group of patients between before and after the HAART era for analysis due to small numbers; it was evident that several cases of chronic HBV arose in the post-HAART era.…”
Section: Incident Hepatitis B Infectionmentioning
confidence: 99%